Basics of process design for 3d freeform-bending - Plettke, Raoul; Vatter, Peter; Vipavc, Daniel (Steel Research International, 2012)
Three-roll-push-bending is an innovative freeform bending process for the production of complex tube geometries with a variable distribution of curvature and torsion. The process design is complicated since there are a lot of parameters which have an impact on the formation of the bending arc. In industrial application a trial-and-error approach is commonly used. This paper presents a method for the process design of 3-dimensional freeform bended tubes. It defines a format to describe the associated geometries mathematically in a way that corresponds with the machine parameters. The mathematical description is based upon a discrete application of the Frenet-Serret formulations on common CAD file formats. The correlation between process parameters and resulting geometry, given by its curvature and torsion, has been examined. Moreover, the paper describes how to retrieve suitable process parameters using a characteristic map. The method can be utilized in process design, as well as to identify the parameters of a bended tube for quality control purposes. It was applied and first sampling points are presented. To describe the linear dependency between the rotation of the feeding arm and the tube's torsion, a new variable called the torsion adjustment coefficient will be introduced. © 2012 Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim.
LFT Import::2019-07-29 (1784)
Keywords: Process design; Three-roll-push-bending; Tube bending

Comparison of new analytical an numerical approaches to model the three-roll-push-bending process - Plettke, Raoul; Vatter, Peter (International Journal of Mechatronics and Manufacturing Systems, 2014)
Freeform bent tubes can be produced with the highly flexible three-roll-push-bending. The process has been fundamentally investigated in recent research by numerical simulation using shell or volume elements. However, because of the large aspect ratio of tube length to wall thickness, computation time required is high. This prohibits the integration in analysis routines to predict the resulting geometry online. In this contribution, the basics of two new approaches are presented to compute the resulting bending radius of two-dimensional freeform bends requiring significantly less computation time. The first approach is based on an analytically derived moment-curvature relationship considering realistic flow behaviour. In the second one, a numerical method is developed using beam elements. The results are compared to experimental data and to numerical results using shell elements for steel and aluminium tubes.
LFT Import::2019-07-29 (1967)
Keywords: Aluminium tubes; Beam elements; Bending theory; Finite-element-model; Flexible manufacturing system; Freeform bending; Modelling; Shell elements; Steel tubes; Three-roll-push-bending; Tube bending

Creation of the Data Base for the Process Design of the Three-Roll-Push Bending Process - Hagenah, Hinnerk; Vipavc, Daniel; Vatter, Peter; Cojutti, Massimo; Plettke, Raoul (7th CIRP Int. Conf. Intelligent Computation in Manufacturing Engineering, 2010)
LFT Import::2019-08-05 (136)

Development of a damage prediction system for bending and cutting of high strength steels - Vatter, Peter; Hildering, Sven; Tsoupis, Ioannis; Merklein, Marion (Key Engineering Materials, 2013)
The application of modern high-strength low-alloy steels (HSLA) and advanced high strength steels (AHSS) for structural and safety relevant components in the automotive industry offers the advantage of combining low specific weight with high material strength. Typical manufacturing processes for these steel grades are bending and cutting operations. However, the forming and cutting potential of these innovative steel grades is different to conventional steels as the process and the damage behaviour is changing. In bending operations cracks occur at the outer bending edge, whereas in cutting operations delamination can appear at the sheared edge, which can initiate component failure. In the scope of this work a method is presented to describe the damage behaviour of both, bending and cutting operations, by theoretical meta models. In order to generate a database experiments were carried out using a typical HSLA. The main influencing factors have been varied experimentally, such as the rolling direction, normalised bending radius and punch to die clearance. To calculate further sampling points a finite element model has been developed and validated against the experimental data. The damage criterion of LemaÎtre has been applied. The necessary parameters were determined by reverse numerical identification by means of the major strain for the bending operation and by the punch force-punch stroke curve for the cutting operation. To build up a system for the prediction of the damage the gained data basis was approximated by mathematical functions. An error analysis was carried out showing good accordance. In doing so, a meta model for the evaluation of the damage rate could be established. The functions were implemented in a software tool which allows the user to determine the failure probability for a given parameter set. This software tool is exemplarily validated against experimental air bending tests using a higher normalised bending radius. Copyright © 2013 Trans Tech Publications Ltd.
LFT Import::2019-07-29 (1853)
Keywords: Bending; Cutting; Damage prediction; High strength steel

Einfluss der Fließkurve auf den Rohrbiegeradius - Merklein, Marion; Vatter, Peter; Plettke, Raoul; Grüner, Martin (wt Werkstattstechnik - Online, 2012)
LFT Import::2019-07-29 (1816)

Geometrical variations of tubes and their impact on freeform bending processes - Vatter, Peter; Plettke, Raoul (Advanced Materials Research, 2013)
In bending processes for tubes and profiles, the produced bending geometry depends on the characteristics of the semifinished product. Tubes are subjected to scatter and deviations from the standard's dimensions caused by their fabrication process. This results in deviations of the forming behaviour. Depending on the bending process, the effect of this phenomenon is even larger, if the deviation of process forces leads to a significant deflection of the die elements. Particularly kinematic bending processes, e. g. the 3-roll-push-bending process have shown to be highly sensitive to low machine stiffness. The effect of this factor has not been identified among the influences of other disturbance factors so far. As an additional aspect, the tube dimensions affect the material characterization which leads to inaccurate material properties in numerical simulations. This results in wrong input data for the process design and has to be corrected in lengthy adjustment procedures. In this contribution the scatter of some geometrical tubes properties and its impact on the 3-rollpush- bending process is investigated. The tube geometry is measured by a tactile measurement system and is compared to the product standards. Observed deviations are categorized according to DIN 4760. The impact of the deviations on the bending process is examined by numerical variant calculations. Besides the tube dimensions, the stiffness of the machine is varied and the influence determined. By considering the errors resulting from wrong input data in the material characterization the overall error is quantified. © (2013) Trans Tech Publications, Switzerland.
LFT Import::2019-07-29 (1885)
Keywords: Batch variations; Bending; Finite element method (FEM)

Influence factors of three-roll-push-bending - Plettke, Raoul; Vipavc, Daniel; Vatter, Peter (Proc. 1st Int. Tube and Profile Bending Conf., 2011)
LFT Import::2019-08-05 (1760)

Investigation on the Process Parameters and Process Window of "Three-Roll-Push-Bending" - Plettke, Raoul; Vatter, Peter; Vipavc, Daniel; Cojutti, Massimo; Hagenah, Hinnerk (Proc. 36th Matador Conf., 2010)
LFT Import::2019-08-05 (129)

New approaches to determine the bending contour of the 3-roll-push-bending process - Vatter, Peter; Plettke, Raoul; Merklein, Marion (7th Int. Conf. on Design and Production of Machines and Dies/Molds, 2013)
LFT Import::2019-08-05 (1880)

Process model for the design of bent 3-dimensional free-form geometries for the three-roll-push-bending process - Vatter, Peter; Plettke, Raoul (Procedia CIRP, 2013)
LFT Import::2019-07-29 (1851)
Keywords: 3D; FE; Free-form bending; Process design; Three-roll-push-bending

Sensitivitätsanalyse des 3-Rollen-Schubbiegens auf Basis der Finite Elemente Methode - Vatter, Peter (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2015)
The three-roll-push-bending process is a kinematic bending process, which can be used to manufacture almost arbitrarily curved 3-dimensional tube components. A disadvantage compared to conventional tool-bound bending processes is the lower repeat accuracy. This book informs operators as well as machine designers about the causes of process deviations. Additionally, the cause-effect relationship between the input parameters and the geometry parameters is described. By this, measures can be deduced to enhance the process robustness in industrial applicatio